PENGEMBANGAN OBJEK WISATA BONO OLEH DINAS KEBUDAYAAN PARIWISATA PEMUDA DAN OLAHRAGA DI KABUPATEN PELALAWAN - Siti Srilestari; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Tourism development is one of the effects of the implementation of regional autonomy . Tourism is also a potential area that should be developed to improve the economic welfare of society . Construction and development of travel of Bono did not experience significant changes , so that the infrastructure facilities have not been constructed thoroughly. This research is aims to determine the potential of which is owned by the attraction of Bono and to describe the development as well as factors inhibiting and supporting the implementation of tourism development Bono by Department of Tourism CultureYouth and Sports Pelalawan.This research is Management uses the theory by Suwantoro. this theory consists of the Tourist attraction, tourist facilities and tourism infrastructure. This type of research is qualitative methode and with techniques data using interviews , observation and documentation .The results of the research is implementation of development tourist attraction of Bono in district Pelalawan has not been realized with good. because inhibiting factos implementation tourism development of Department of Tourism CultureYouth and Sports Pelalawan. by natural actor and the lack of people participation.Key Word: Development, tourist attraction, Bono, Pelalawan